The Immigrant Welfare Effect: Take-Up or Eligibility? - Edward J. Bird; Hilke Kayser; Joachim R. Frick; Gert G. Wagner (Institute for the Study of Labor (IZA), 1999)
Are immigrants on welfare because they are more likely to be eligible or because they are more likely to claim benefits for which they are eligible? The answer is politically important, but because most current research on immigration and welfare is based on data from the U.S., the answer is difficult due to the complexities of the transfer system which make eligibility determinations difficult. In Germany, by contrast, eligibility for the main cash transfer program, Sozialhilfe (Social Assistance), is determined by a comparatively simple nation-wide formula. We use data from the German Socio-Economic Panel to test whether immigrants to Germany are more likely than natives to claim welfare benefits for which they are eligible. We find that immigrants are more likely than native Germans to receive welfare, both because immigrants are more likely to be eligible, and because they are more likely, when eligible, to claim their benefits. However, we also find that this greater propensity to take-up benefits is not related to immigrant status per se: when other socio-demographic factors are accounted for in an appropriate manner, immigrant households are no more likely to take up benefits than native households.
Keywords: J61; H53; I38; 330; Immigration; social assistance; eligibility; take-up; Einwanderung; Ausländer; Sozialhilfeempfänger; Soziale Mindestsicherung; Schätzung; Deutschland